CHARACTERS’ READER EXPERIENCE AS A CRITERIA OF LIFE COMPLETENESS IN THE CREATIVE WORLD OF A “EUGENE ONEGIN” - Tatyana A. Pakhareva (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
In the article we review a problem of a literature value status in the creative world of an A. Pushkin novel “Eugene Onegin”. While analyzing the spheres of both an author’s and main character’s speech in the verses dedicated to the Onegin’s reading, we discovered that an ability to actively exist in both conventionally vital and literature spaces is one of the main criteria of life authenticity and fullness in the novel’s value system. Moreover, an author’s vision of a literature world is reflected in the novel’s poetics. To our mind, author sees the literature world as a universum which is a source of the value benchmarks and is connected with the life basics – the deepest levels of Eros and Thanatos as well as spheres of public activities and family formed on the social level. The author’s holistic worldview as a literature-centered person is contrasted in the novel to the hero’s worldview devoid of ontological fullness. This fundamental difference between the hero and the author is clearly seen in those fragments of the text where their points of view are side by side in the narration – for example, in Chapter XLIV, Chapter I (“And once again to idleness consigned...” (hereinafter “Eugene Onegin” translation by V. Nabokov is used)). The position of the hero here signals that he does not have a complete world view: he languishes in “emptiness”, and an attempt to grab someone else’s intellectual experience is a way to fill it, while the hero tries to deal with spiritual emptiness in a purely rational way – appropriating “someone else’s mind”. That is why his reading experience turns out to be untenable and results in fruitless hypercriticism. The literary-centric position of the author, through which the ontological completeness of world perception is revealed, is manifested in this stanza in the system of likening books to the basic foundations of being. It is the author, not the hero, who consistently likens the books to: 1) a military detachment, the image of which actualizes the socio-historical context (“He crammed a shelf with an array of books” (“otriad” in original text means “squad”, “brigade”; in Nabokov’s translation this meanning is lost)); 2) to women, thereby mating with them a loving-erotic sphere of life (“As he’d left women, he left books”); 3) family, representing the level of blood-relationship (“with its dusty tribe the shelf”). Finally, in the last stanzas in the image of the “funerary taffeta” in connection with the world of books, the context of death is also actualized, without which the ontological horizon of the book world would be incomplete. Thus, the world of literature from the point of view of the author, manifested in the analyzed stanza through a system of comparisons, is life itself in its entirety and simultaneity of the presence of all defining principles in it. And from the rationally limited point of view of the hero, this is just a dead set of words in which something is always missing. The opposition of the author and the hero according to the criterion of the ontological completeness of the world perception and the connection of this completeness with their reading experience is traced throughout the text of the novel. From this point of view, the article, in particular, analyzes fragment VIII of the chapter, in which Onegin again tries to get out of the mental crisis with the help of reading. The context of not only the novel, but also the lyrics of Pushkin, is drawn to the analysis of this fragment. The difference between the ideological positions of the hero and the author appears especially vividly when comparing the overlapping fragments of this stanza and the poem “Remembrance” (“When, for the mortal one, is stilled the noisy day...” (transl. by Yevgeny Bonver)).